Brand Image and Social Influence Analysis on Students' Decisions in Choosing Private University With Digital Marketing as Moderating - Wulandari, Novri; Gunarto, Muji (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research analyzes brand image and social influence on students' decisions in choosing private universities, with digital marketing as a moderating variable. Private universities increasingly utilize digital marketing to increase their visibility and attractiveness in the current digital era. This study uses quantitative methods with a survey of prospective students as respondents. The collected data was analyzed using multiple regression analysis techniques to identify the relationship between brand image, social influence, and student decisions, as well as the role of digital marketing in strengthening or moderating this relationship. The research results are expected to provide insight into how brand image and social influence influence college selection decisions and how digital marketing can be used to increase the effectiveness of private higher education marketing strategies. This research can help private university managers formulate marketing strategies that are more effective and relevant to the needs and preferences of prospective students. Based on analysis of variables that have a significant influence on student decisions, namely brand image, digital marketing and social influence